Kepemimpinan Ideal Versi Komunitas Forum Online - Irwansyah Irwansyah (CommLine, 2015)
Leader and leadership states between ideological and cultural discourses. These discourses are not only occurred in the real world but also in the virtual world particularly in an online community forum. By using East and West leadership concepts and netnog raphy method in text discourses, this study finds that there is netizen level categorization in giving comments and opinions in the forum. Transactional leadership is prefered by Kaskuser netizen than transformational leadership. Leader who makes a change, work ori ented, and has the East accent, is ideal figure of online commuity forum. Although, expecta tion and need of forum online community member which are devided into Kozinets netizen level, are not depicted according to level of observed online community forum.